Cliff-like NiO/Ni3S2 Directly Grown on Ni Foam for Battery-type Electrode with High Area Capacity and Long Cycle Stability. (10th October 2017) - Yan, Zeying; Guo, Chunli; Yang, Feng; Zhang, Chunchen; Mao, Yuqiong; Cui, Suxia; Wei, Yinghui; Hou, Lifeng; Xu, Lichun
Abstract: Cliff-like NiO/Ni3 S2 directly grown on nickel foam is fabricated by a mixed method of hydrothermal and thermal decomposition, which is directly used as the working electrode without any binder and other conductive additive assistants. The NiO/Ni3 S2 electrode can deliver a high area capacity of 2.28C cm −2 at 2 mA cm −2, along with outstanding cycling stability (102% capacity retention after 10000 cycles). The energy density of the NiO/Ni3 S2 //AC hybrid device is 158.37 Ws g −1 at a power density of 0.23 W g −1 (93.71 Ws g −1 at 2.31 W g −1 ). Compared with other NiO composites on nickel foam, these results indicate that NiO/Ni3 S2 directly grown on Ni foam opens up the potential application for energy-storage devices with high area capacity and high cycling performance.